Strengthening Family Resilience through Family Finance Norms: Between Traditions and Modernity - Nizami, Auliya Ghazna; Hidayatulloh, Hidayatulloh; Abadia, M. Kurnia Rahman (ADDIN, 2025)
This article examines the normative foundations of family finance in Islam and their pivotal role in strengthening family resilience through a normative-doctrinal analysis of classical Islamic jurisprudence texts, including works by Al-Kasani, An-Nawawi, Ibn Qudamah, and contemporary scholarly interpretations. The study analyzes primary sources from the four major madhāhib (legal schools), Quranic verses, and authenticated hadith collections, while critically engaging with contemporary theories of family resilience and household economics from scholars such as Becker, Putnam, and empowerment theorists. This research employs no empirical data or case studies but focuses entirely on doctrinal analysis and theoretical synthesis. By synthesizing traditional Islamic teachings with modern socio-economic discourses, this research highlights how Islamic financial norms, rooted in concepts of responsibility (mas’ūliyyah), moderation (i’tidāl), and trust (amānah), contribute not only to economic stability but also to the adaptive capacity and emotional well-being of families in the face of changing social realities. This study argues that Islamic family finance norms offer a comprehensive framework that fosters both material sufficiency and holistic resilience, thus demonstrating the dynamic applicability of Islamic legal values in contemporary family life.